Catalytic Selective Oxidation of β-O-4 Bond in Phenethoxybenzene as a Lignin Model Using (TBA)5[PMo10V2O40] Nanocatalyst: Optimization of Operational Conditions - Juan Díaz; Luis R. Pizzio; Gina Pecchi; Cristian H. Campos; Laura Azócar; Rodrigo Briones; Romina Romero; Eduardo Troncoso; Camila Méndez-Rivas; Victoria Melín; Juan C. Murillo-Sierra; David Contreras (Molecules, 2023)
The catalytic oxidation of phenethoxybenzene as a lignin model compound with a β-O-4 bond was conducted using the Keggin-type polyoxometalate nanocatalyst (TBA)5[PMo10V2O40]. The optimization of the process’s operational conditions was carried out using response surface methodology. The statistically significant variables in the process were determined using a fractional factorial design. Based on this selection, a central circumscribed composite experimental design was used to maximize the phenethoxybenzene conversion, varying temperature, reaction time, and catalyst load. The optimal conditions that maximized the phenethoxybenzene conversion were 137 °C, 3.5 h, and 200 mg of catalyst. In addition, under the optimized conditions, the Kraft lignin catalytic depolymerization was carried out to validate the effectiveness of the process. The depolymerization degree was assessed by gel permeation chromatography from which a significant decrease in the molar mass distribution Mw from 7.34 kDa to 1.97 kDa and a reduction in the polydispersity index PDI from 6 to 3 were observed. Furthermore, the successful cleavage of the β-O-4 bond in the Kraft lignin was verified by gas chromatography–mass spectrometry analysis of the reaction products. These results offer a sustainable alternative to efficiently converting lignin into valuable products.